Acoustic Emission and Specific Film Thickness for Operating Spur Gears - Raja Hamzah, R. I.; Mba, D. (American Society of Mechanical Engineers, 2007)
This paper presents experimental results correlating acoustic emission (AE) activity and the specific film thickness () for operational spur gears. This relationship was established by spraying liquid nitrogen onto a rotating gear wheel, thereby reducing its operating temperature and controlling the specific film thickness for a range of load and speed conditions. It is concluded that the level of AE activity is dependent on the specific film thickness and the source of AE during meshing is predominately due to asperity contact. Furthermore, measurements of AE activity may offer an opportunity to quantify the level of asperity contact for meshing gears under a range of operating conditions.